Memórias e percepções de alunos da graduação sobre o uso de recursos da internet para aprendizagem - Costa, Francielle da Rosa (2020)
This work aimed to investigate memories about experiences related to the use of internet resources during High School and perceptions about the use of these resources in learning at the beginning of Higher Education. The research was carried out through a questionnaire that explored the students' memories about habits and uses of the internet in the final phase of Basic Education and their perceptions about the use of texts and videos in the learning process. Fifty-seven first semester students of a course in the health area participated in the research. Data on the presence of computer labs in schools, associated with results on frequency of access and places where students use the internet, indicate that the school was not the main place for the development of competences or skills in the use of digital resources for learning. The answers to the questions about students' preferences regarding videos, video lessons and texts reveal that videos and video lessons are considered useful for content review and printed books are more valued than digital texts. The results reinforce the need for a broader discussion on the use of the internet for learning formal high school content without teacher mediation. The existence of rejections in relation to digital resources as learning aids indicates the need for teaching strategies that mix the use of physical and digital resources, especially for beginners in higher education. The indication and availability of varied resources continues to be the best recommendation to reach the largest number of students and meet individual needs. The data also point to the need for more formal approaches to the use of internet resources for academic research, both in relation to the reliability of the information and the correct use of the collected material.